Directed differentiation of human embryonic stem cell‐line HUES9 to dopaminergic neurons in a serum‐free defined culture niche. (19th November 2012) - Datta, Indrani; Ganapathy, Kavina; Tattikota, Surendra Mohan; Bhonde, Ramesh
Abstract Although there are several reports on differentiation of human embryonic stem cells to dopaminergic neurons, notable heterogeneity exists in the reported yields of tyrosine hydroxylase (TH)‐positive cells. For benchmarking performance and efficiency standards in future applications of hESC‐derived dopaminergic neurons, there is thus a dire need of well‐defined directed differentiation protocols. Pal et al. [Pal et al. 2009 Exp Biol Med (Maywood) 234:1230–3] demonstrated predisposition of HUES9 towards ectodermal lineage, but the directed differentiation of HUES9 to dopaminergic neurons has not yet been reported. Therefore, we report here a simple two‐step protocol using suitable ECM and serum‐free induction medium for generating dopaminergic cells from HUES9‐derived embryoid bodies. Flow cytometry analysis of the neural progenitors obtained after the first step gave an enriched yield of cells immune‐positive for nestin (99.6 ± 0.1%), musashi12 (98.1 ± 1.5%) and Sox2 (95.4 ± 2.6%). Most of these cells also expressed the proliferation marker Ki67 (83.8 ± 1.5%), whereas the presence of the undifferentiated stem cell marker Oct4 was negligible. In the second step, when these neural progenitors were exposed to midbrain cues sonic hedgehog and fibroblast growth factor 8 along with bFGF, the differentiated cells showed an upregulation of dopaminergic‐related transcription factors Nurr1 and Engrailed1. Immunocytochemistry and flow cytometry analysis showed that these differentiated cells were positive for the mature neuronal marker Map2ab (96.2 ± 1.5%) and dopaminergic neuronal marker TH (71.9 ± 4.4%). Thus, the data demonstrate novel findings of the directed differentiation of HUES9 to dopaminergic neurons using well‐defined serum‐free nutrient supplements.